Is it possible to reform police stops? Politicisation and police change in two European countries - Maillard, Jacques de (Criminology & criminal justice, 2024)
In several Western countries, police stops have become the object of political controversies on what the objectives and targets of police activities should be. By using the examples of two European countries (France and Scotland) where the issue has been highly politicised over the last 15 years, we will conduct a comparative analysis to show how it has led to significant change in legislation, policy and police practice in Scotland and yet to a policy blockage in France. In both cases, police stops have been politicised through the combination of three interlinked axes: the production of critical scientific evidence, intense media coverage and forceful political attention. Differing national traditions are not sufficient to explain the divergent outcomes. Drawing upon historical institutionalism, we will underline how institutions, understood as stable sets of formal and informal rules, favour certain policy developments rather than others. We will explore how each political context has shaped the balance of constraints and opportunities for reform and we will stress the importance of the respective dynamics of reforms. While both jurisdictions experienced ‘hot’political climates, certain conditions needed to be met in order for significant reform to manifest.